Are the Ideology, Values, Principles, and Identity of Cooperatives Shifting? A Lesson from Indonesia - ., Subagyo; Salim, Ubud; ., Djumahir; Djazuli, Atim (Journal of Ecohumanism, 2025)
Cooperatives have been a foundation for the Indonesian economy, however, there is a change in their operations. Therefore, this study aims to comprehend the implementation of university cooperatives toward the dynamic changes and explores the shift in ideology, values, principles, and identity of cooperatives. This study used a qualitative study with a phenomenology approach and involved eight selected informants to be interviewed using semi-structured interviews. The results disclosed that there is cooperatives identity transformation, shifting in cooperative principles, and mutual cooperation practice. In addition, it found challenges in maintaining cooperative ideology and deliberation value in decision-making. Lastly, identity and relevance crises are also the main issues in the majority of cooperatives in Indonesia. The insights gained will enable some parties, including government, academics, practitioners, and members to jointly revitalize the cooperative spirit, and ideological substance, and assert its relevant values.